How to Evaluate Augmented Reality Embedded in Lesson Planning in Teacher Education - Anna Henne; Sabrina Syskowski; Manuel Krug; Philipp Möhrke; Lars-Jochen Thoms; Johannes Huwer (MDPI AG, 2024)
Augmented reality (AR) is vital in education for enhancing learning and motivation through interactive environments and experiments. This requires teacher training in AR creation and integration. Research indicates that learning effectiveness relies on thorough preparation, calling for the development of scoring rubrics for evaluating both educational AR and AR's educational integration. However, no current studies provide such a rubric for assessing AR's pedagogical implementation. Hence, a scoring rubric, EVAR (Evaluating Augmented Reality in Education), was developed based on the framework for the analysis and development of augmented reality in science and engineering teaching by Czok and colleagues, and extended with core concepts of instructional design and lesson organization, featuring 18 items in five subscales rated on a four-point Likert scale. To evaluate the validity and reliability of the scoring rubric, AR learning scenarios, designed by eleven master's seminar pre-service teacher students at the University of Konstanz, majoring in biology, chemistry, or physics, were assessed by five AR experts using the newly developed scoring rubric. The results reveal that a simple classification of AR characteristics is insufficient for evaluating its pedagogical quality in learning scenarios. Instead, the newly developed scoring rubric for evaluating AR in educational settings showed high inter-rater reliability and can discriminate between different groups according to the educational quality of the AR and the implementation of AR into lesson planning.